Comparing primary care pediatricians' perceptions of clinics with and without integrated behavioral health. (2019) - Lancaster, Blake; Cook, Andrew; Bruni, Teryn; Sturza, Julie; Sevecke, Jessica; Ham, Hannah; Knight, Rachel; Hoffses, Kathryn; Wickham, Cheryl A.; Orringer, Kelly A.
Abstract: Objective: The purpose of this study was to investigate primary care pediatrician (PCP) perceptions of prevalence of, time spent in, and satisfaction with behavioral health services across clinics with and without on-site behavioral health providers (BHPs). Methods: A cross-sectional survey design was used to examine satisfaction across sites. Data were collected on PCP perceptions of behavioral health services among 60 pediatricians within two academic medical systems. Results: PCPs perceived behavioral health issues are prevalent and a time-consuming aspect of medical appointments and preferred to have on-site BHPs over off-site referral sources. Compared to sites without an on-site BHP, sites with on-site BHPs were more satisfied with behavioral health service availability and resources, felt they spent more time addressing medical concerns, and spent less time providing anticipatory guidance. Discussion: Study limitations included questions surrounding the validity of survey items to accurately assess PCP perceptions, lack of rigorous experimental design, and reliance on self-report data.